Survey of some broadcasting ideas from Eric Boden to John MacDonagh, - Boden, Eric
Survey of some broadcasting ideas from Eric Boden, managing director of 'Schwerin Research Company Ltd.', to John MacDonagh at the radio department of the Hospitals' Trust, Radio Eireann. Eric Boden is offering John some suggestions to implement in the radio shows on Radio Eireann.